Crystalline polymer nanofibers with ultra-high strength and thermal conductivity - Ramesh Shrestha (Nature Portfolio, 2018)
Polymers compared to structural materials usually have low strength and thermal conductivity. Here the authors show a fabrication method to form bio-compatible crystalline polyethylene nanofibers that exhibit ultra-high strength, thermal conductivity and electrical insulation.